Knowledge sharing on social media: state of the art in 2018 - Mladenović, Dušan; Krajina, Anida (Journal of Business Economics and Management, 2020)
In the past decade, the importance of social media has increased, especially in knowledge sharing practices. Current massive evolution of computer-mediated communication platforms influenced the ways of how knowledge is managed and shared by individuals. This literature review of published papers in the past decade explores the potential of using social media in knowledge sharing by individuals and, through the mapping of the existing studies, identifies research opportunities for future studies. Primary, tacit and explicit knowledge sharing have been investigated. The findings suggest that there are different ways in which knowledge is shared across social media, but the systematic approach and synthesis is challenging to define. Therefore, there are some open courses of future research that may form the basis for a theoretical framework. The results of the present literature review should increase methodological rigor, and provide the guidelines to academics by identifying research opportunities. They can also serve as a comprehensive collection of findings for knowledge management decision makers. First published online 15 November 2019